Kapag sumalupa ang gunita piling journal entries - Sikat, Rogelio 1940-1997; Ateneo de Naga University Press (Naga City Ateneo de Naga University Press, 2018)
Author's account on his selected essays.
In Tagalog.
Keywords: Sikat, Rogelio -- 1940- -- Diaries; Feature writing; Journalism -- Authorship